SWOT Analysis of Puzzle 3D Modeling-Based Learning on Neural System Materials - Niyar Ana Qodariyah; Slamet Hariyadi; Rayendra Wahyu Bachtiar (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
The research is based on challenges in learning, especially in nervous system material, where there are often misconceptions in students about the course of neural impulses and understanding the structure of the nervous system in humans. The purpose of the research is to develop learning media in the form of 3D-MbL puzzle media to help junior high school students understand the concept of nervous system material and conduct a SWOT analysis of the learning media. The research method used is qualitative descriptive, with data collection techniques through observation, documentation, and questionnaires. The instrument used in this study is a validation sheet by two validators, namely material validation and media validation. 3D-MbL puzzle media is made using several tools and materials, with the main ingredients being made using flannel and analyzed using the SWOT method. The study's primary results show that 3D-MbL puzzle media can attract students' interest and hone creative thinking skills during learning. However, there are challenges, such as the media needing help to explain in detail the process of neural impulses and other essential concepts in the material of the nervous system. The opportunity of this 3D-MbL puzzle media can be used as an exciting anatomy of the human body, and the threat is that students do not understand how to use it if the teacher does not clearly explain the use of the media. In conclusion, 3D-MbL puzzle media for the nervous system offers innovations in delivering science learning materials. However, further improvements are needed so that this media can be more optimal in delivering learning materials.